Efektivitas Pelaksanaan Pendidikan Sosial dan Finansial melalui Home Education Play di PAUD Inklusif - Fatimah Zahro, Ifat; Dwi Tresna Santana, Fifiet; Robiyyah, Robiyyah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to determine the effectiveness of the implementation of social and financialeducation through Home Education Play in inclusive PAUD. Home Education Play (HEP) is a form of involving parents at home with play activities to improve the character of sharing, saving, saving and responsibility. This research was conducted using a qualitative approach, and was conducted at the PAUD Melati 06 Cimahi Post which is an PAUD that organizes inclusive education. The results of the study are as follows: (1) The existence of parents / family involvement in the implementation of social and financial education in PAUD Melati 06 Post; (2) Applying the Home Education Play method, effective to improve the ability of social education and financial early childhood